Reduction of ICD Shock Burden by Eliminating Back‐Up Pacing Induced Ventricular Tachyarrhythmias. (2nd May 2014) - THEIS, CATHRIN; MOLLNAU, HANKE; SONNENSCHEIN, SEBASTIAN; KONRAD, TORSTEN; HIMMRICH, EWALD; BOCK, KARSTEN; SCHULZ, EBERHARD; KÄMPFNER, DENISE; GERHARDT, SIMON; QUESADA OCETE, BLANCA; MÜNZEL, THOMAS; ROSTOCK, THOMAS
ICD Shock Reduction by Subthreshold Pacing: Introduction: Implantable cardioverter defibrillators (ICD) may have the capacity to provoke or worsen ventricular tachyarrhythmias (VT). It has been reported that ICD shocks by itself can increase mortality. This study aimed to determine the role of back‐up pacing‐induced VT (PIT) in the overall ICD shock burden by avoiding pause‐related ventricular back‐up pacing. Methods and Results: A population of 550 single‐chamber ICD patients was studied. Of them, 17 (3%, 69 ± 16 years, 14 male) patients had documented episodes of PIT. A total of 431 VT episodes were documented including 89 (21%) due to PIT. In 3 patients, VT events were exclusively PITs. After ≥2 documented PITs, the pacing output for VVI pacing was set to a subthreshold level resulting in noncapturable ventricular back‐up pacing. All other device parameters remained unchanged to prove a potential proarrhythmic effect of pause related back‐up pacing. During a follow‐up of 99 ± 39 months after reducing the pacing output to a subthreshold level, no further episodes of PIT were observed (P < 0.001). Moreover, with the prevention of PITs, the ICD shock burden decreased significantly (pre: 150 vs. post: 18, P < 0.001). However, a single event of pause‐induced VT occurred due to missing back‐up pacing. Conclusions: PIT is a frequent mechanism of VTs in ICD patients resulting in a substantially increased shock burden. Elimination of pause‐related back‐up pacing by subthreshold pacing output effectively abolishes PIT and thus significantly reduces ICD shock burden.